NARRATIVES OF LIFE: A FEMINIST RESEARCH APPROACH FOR GENERATING CRITICAL REFLEXIVITY - Crocco Valdivia, Alejandra (2024)
From a feminist perspective, we present the possibilities and limits of a qualitative research technique that considers the active participation of people who articulate with the researcher under a critical perspective and with a rescue of their embodied emotional experience, such as the construction of Life Narratives. This feminist method challenges the traditional ways of generating qualitative knowledge by promoting a horizontal relationship between the researcher and the participant and aims to confront the questioned academic extractivism present in contemporary universities. In this case, four Life Narratives were generated with female academics who are or were directors of PhDs in Chilean universities and who led the quality assurance process of their programmes. The limits are presented both technically and also with regard to the effective possibilities of moving traditional structures in the form of knowledge production. Furthermore, although this technique seeks to address feminist criticisms related to leaving corporeality and emotionality out of the research, this incorporation is not always achieved with participants in positions of power. It is concluded that this method allows a critical reflexivity typical of feminist work, unravels the power dynamics present in the processes of knowledge construction and also allows us to see the consequences that research practices have both on the subjects involved and on their contexts.